Análisis de los sitios web y Redes sociales como plataforma de comunicación corporativo de las agencias de comunicación en Sudamérica Caso de estudio Perú, periodo 2017 - Celi Villavicencio, Viviana Carolina (2018)
Abstract:The technological and social development in the communication environment has evolved thanks to the different social platforms that exist on the web, satisfying optimal needs for the benefit of users and companies, giving way to invention, innovation and improvement of said means. Social networks or websites allow companies to get known, have an approach and interaction with their audiences through the generation and publication of content such as news, images, videos, etc. The same that are segmented so that each user can access the information that interests them, additionally these platforms allow the creation of strategic alliances that are aligned under the interest in the business activity. Therefore, in the present investigation it will be possible to know how the 10 communication agencies of Peru already selected, manage their websites and social networks through the creation of databases and web measurement tools, which will achieve the necessary results to the elaboration of the different analyzes, evidencing their competitive advantages and shortcomings of each of them.